Sinestesia música y color: composición de la letra de cuatro temas musicales usando elementos de songwriting, y conceptos y características de los colores: amarillo, azul, negro y blanco según el libro psicología del color de Eva Heller, para ser aplicados en un recital final - Salinas Tamay, Michelle Salomé (2020)
In Music, as a resource, color is utilized to complement, externally, the Interpretation within the Performance, and by no means as a tool for its creation and composition. In this sense, the present project seeks to place significant value to the use of color within music’s creative process. To this end, research on Synesthesia’s study of the relationship between music and color, had to be carried out. Hereunder, and based on Eva Heller’s book, an analysis of the feelings and emotions of color, in relation to the psychology of color, was also undertaken. In addition to these and seeking to facilitate the writing of this project’s original, and unpublished musical themes, the theoretical principles underpinning lyrics in music were also part of this research. Once these concepts had been fully understood, it was possible not only to link tone and color, but also to assign each color a feeling and an emotion. As a result, four colors: yellow, blue, black and white, have been represented by four original, unpublished themes. Since this is a graduation project conceived within the emphasis on the Performance, the main and final objective of this thesis has been to showcase, in a final recital